Enforcing Public-Private Partnership Contract : How do Fiscal Institutions Matter? - Nose, Manabu (IMF Working Papers; Working Paper ;, 2017)
Public-private partnerships (PPPs) have increased rapidly in emerging and developing countries, creating both opportunities and fiscal challenges. One of the main challenges is that while governments have increased commitments in guarantees and direct subsidies to promote PPPs, contractual disputes remain high with significant costs. This paper examines how fiscal institutions affect the selection of PPP contracts and the probability of contract disputes using about 6,000 PPP contract-level data. The analysis shows that larger government financing needs, lower budget transparency and bureaucratic efficiency are associated with higher probability for governments to offer guarantees. Propensity score matching results show that disputes are more common for guaranteed contracts due to adverse selection and contingent liability effects. PPP management quality and budget transparency are found to be key determinants for a longer survival of PPPs.